An implementation science framework to understand low coverage in mass dog rabies vaccination. - Ricardo Castillo-Neyra; Lizzie Ortiz-Cam; Jorge L Cañari-Casaño; Elvis W Díaz; Laura D Tamayo; Guillermo Porras; Sergio E Recuenco; Valerie A Paz-Soldan (PLoS Neglected Tropical Diseases)
Background Dog-mediated human rabies has been greatly reduced in the Americas and eliminated from most high-income countries. However, many countries in Africa, Asia, and parts of Latin America are still struggling with this gruesome disease. Mass dog vaccination, a One Health strategy, is the primary approach for elimination. However, achieving and sustaining appropriate vaccination coverage in endemic areas remains a challenge. Our objective was to apply the Consolidated Framework for Implementation Research (CFIR) in Arequipa, Peru as a guiding tool to understand the barriers faced by different stakeholders. Methods Seven focus groups with 56 participants were conducted to capture community perspectives on rabies and vaccination. A workshop was conducted with two groups of public health personnel (n = 69): mass dog vaccination campaign (MDVC) implementers and authorities, in charge of dog rabies control. With these stakeholders we explored factors contributing to the decrease in MDVC post COVID-19. We used the CFIR approach to understand barriers within five different domains: innovation, outer setting, inner setting, individuals, and implementation. Results Barriers within the community included insufficient communication, a short vaccination period, and fragmented collaboration among health system coordinators. At the individual level, a decreased perception of rabies risk occurred as both people and their dogs spent more time indoors due to the COVID-19 pandemic (in urban areas). Dog vaccination was deprioritized compared to COVID-19 protection, with individuals focusing on their own vaccinations and avoiding crowded spaces. In periurban areas, longer work hours due to the pandemic's financial impact left less time for dog vaccinations on weekends. Participants reported confusion caused by private veterinarians, who claimed that government-subsidized vaccines were of poor quality. Among implementers and authorities, the main barriers included insufficient MDVC materials and equipment, unclear responsibilities, and a lack of time to evaluate the campaign after activities. Importantly, financial constraints and fragmented commitment from higher-level institutions posed challenges for proper planning and implementation. Conclusions We identified barriers and co-designed strategies to improve MDVC participation including strengthening municipal alliances, virtual and physical publicity for events within districts, adequate training for vaccinators, reinforcing vaccinators to remain in fixed spots, and expanding vaccination campaign hours.